Short-term interval training alters brain glucose metabolism in subjects with insulin resistance - Honkala, Sanna M; Johansson, Jarkko; Motiani, Kumail K; Eskelinen, Jari-Joonas; Virtanen, Kirsi A; Löyttyniemi, Eliisa; Knuuti, Juhani; Nuutila, Pirjo; Kalliokoski, Kari K; Hannukainen, Jarna C (Journal of cerebral blood flow and metabolism, 2018)
Brain insulin-stimulated glucose uptake (GU) is increased in obese and insulin resistant subjects but normalizes after weight loss along with improved whole-body insulin sensitivity. Our aim was to study whether short-term exercise training (moderate intensity continuous training (MICT) or sprint interval training (SIT)) alters substrates for brain energy metabolism in insulin resistance. Sedentary subjects (n = 21, BMI 23.7–34.3 kg/m2, age 43–55 y) with insulin resistance were randomized into MICT (n = 11, intensity≥60% of VO2peak) or SIT (n = 10, all-out) groups for a two-week training intervention. Brain GU during insulin stimulation and fasting brain free fatty acid uptake (FAU) was measured using PET. At baseline, brain GU was positively associated with the fasting insulin level and negatively with the whole-body insulin sensitivity. The whole-body insulin sensitivity improved with both training modes (20%, p = 0.007), while only SIT led to an increase in aerobic capacity (5%, p = 0.03). SIT also reduced insulin-stimulated brain GU both in global cortical grey matter uptake (12%, p = 0.03) and in specific regions (p < 0.05, all areas except the occipital cortex), whereas no changes were observed after MICT. Brain FAU remained unchanged after the training in both groups. These findings show that short-term SIT effectively decreases insulin-stimulated brain GU in sedentary subjects with insulin resistance.